2017
DOI: 10.5194/os-13-503-2017
|View full text |Cite
|
Sign up to set email alerts
|

Spatial distribution of turbulent mixing in the upper ocean of the South China Sea

Abstract: Abstract. The spatial distribution of the dissipation rate (ε) and diapycnal diffusivity (κ) in the upper ocean of the South China Sea (SCS) is presented from a measurement program conducted from 26 April to 23 May 2010. In the vertical distribution, the dissipation rates below the surface mixed layer were predominantly high in the thermocline where shear and stratification were strong. In the regional distribution, high dissipation rates and diapycnal diffusivities were observed in the region to the west of t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(15 citation statements)
references
References 59 publications
4
11
0
Order By: Relevance
“…Our understanding of turbulent mixing in the SCS has been improved in the past years. Studies of spatial structure and temporal variability of turbulent mixing in the SCS have been carried out successively 4,69 . These studies revealed that enhanced mixing with diapycnal diffusivity of 10 −3 m 2 /s, being two orders of magnitude larger than that in the Pacific Ocean, occurs in the deep SCS and it is highly variable in both space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Our understanding of turbulent mixing in the SCS has been improved in the past years. Studies of spatial structure and temporal variability of turbulent mixing in the SCS have been carried out successively 4,69 . These studies revealed that enhanced mixing with diapycnal diffusivity of 10 −3 m 2 /s, being two orders of magnitude larger than that in the Pacific Ocean, occurs in the deep SCS and it is highly variable in both space and time.…”
Section: Introductionmentioning
confidence: 99%
“…Shang et al . 22 found that MG parameterization can be applied in the upper ocean of the South China Sea.…”
Section: Introductionmentioning
confidence: 99%
“…The methods we use are the non-linear regression and iterative methods commonly used in the study of Natural science [17][18][19][20] . Compared with the Susceptible-Infected-Removed (SIR) and Susceptible-Exposed-Infectious-Recovered (SEIR) models used in epidemiology, our method is simple, accurate, and reliable.…”
Section: Resultsmentioning
confidence: 99%